Genetic analysis of Intron 2 of Muscling Gene Myostatin (MSTN) and its association with morphometric in Dorper sheep - Sutopo, Sutopo; Febriana, Achiriah; Lestari, Dela Ayu; Setiaji, Asep; Kurnianto, Edy; Mustofa, Fatmawati; Rivanda, Iqbal Ash Shidiqie (Journal of Advanced Veterinary Research, 2026)
Myostatin (MSTN) acts as an inhibitor of skeletal muscle growth, and genetic variations in this gene are known to affect growth performance in livestock. This research explored the genetic variation in intron 2 of the MSTN gene and its correlation to morphometric traits in Dorper sheep. The study involved 42 animals, including nine imported Australian Dorper (G0) and 33 offspring (G1). Genomic DNA was extracted from blood samples, and a 1078 bp segment of MSTN intron 2 was amplified and sequenced. The morphometric traits assessed were body weight (BW), body length (BL), withers height (WH), chest depth (CD), chest width (CW), chest girth (CG), rump height (RH), and rump width (R). Sequence analysis revealed a single nucleotide polymorphism (SNP), rs406265773, with genotypic frequencies of 0.81 (AA), 0.14 (AC), and 0.05 (CC), and allelic frequencies of 0.88 (A) and 0.12 (C). The observed and expected heterozygosity were 0.14 and 0.21, respectively, indicating a deviation from Hardy–Weinberg equilibrium (χ² = 4.27). Both haplotype and nucleotide diversity were found to be low. Significant correlations were found between MSTN genotypes and several morphometric traits. These findings suggest that rs406265773 could be a useful genetic marker for growth related traits in Dorper sheep, potentially aiding marker assisted selection in breeding programs.